The Effect of PVP on The Molecular Interaction, Crystallinity, and Morphology of Biopolymer Film: A Review - Girsang, Gabriela Chelvina Santiuly; Khoerunnisa, Fitri; Anwar, Budiman (Green Engineering Society, 2024)
Blending of biopolymers with other polymers i.e. PVP (polyvinylpyrrolidone) is expected to improve the processability and properties of biopolymer-based films. This blending leads to the new molecular structures due to interactions between the polymers, which affect the crystallinity and morphology of the films, as results, enhance the mechanical, optical, and thermal properties of the biopolymer/PVP films. This review aims to provide an overview of the effect of PVP on the molecular interactions, crystallinity, and morphology of biopolymer films. such as chitosan, ethyl cellulose (EC), hydroxyethyl cellulose (HEC), and hydroxypropyl methylcellulose (HPMC). PVP can form hydrogen bonds with chitosan, HEC, and HPMC. Incorporating PVP with HPMC and HEC results in a uniform film morphology, whereas higher PVP ratios in chitosan/PVP blends can cause cracks, indicating the necessity for an optimal ratio to achieve a homogeneous matrix. The addition of PVP to EC results in discoidal features within the film matrix, signifying separate phases and immiscibility between PVP and EC. PVP also able to disrupts the semicrystalline structure of HEC and HPMC, making the film more amorphous.